UNCERTAINTY OF MEASUREMENT RESULTS IN FUEL ANALYSES - Couto, Paulo Roberto Guimarães; Lemos, Ilse Maria Guilhermino (Revista de Engenharia Térmica, 2002)
The result of a measurement serves as a parameter in a variety of applications, such as: the sale of products; the inspection of materials in relation to specifications/ limits set by a standard; providing support for a judicial ruling; improving the specific quality of products; estimating profitability and making comparisons with a view to mutual recognition between metrology laboratories and systems. The aim of this work is to demonstrate the relevance and applications of the ISO GUM 95 in the fuel analyses conducted by the LABCOM at the EQ/UFRJ, presenting results tables and discussions. The paper further discusses the strategic importance of metrological reliability of measurement results and of the actions of a laboratory within the context of the science of metrology in Brazil.